Automaed Short Esai Scoring (ASES): Sebuah Solusi Potensial Untuk Model Penilaian Kurikulum Kebencanaan dalam Sistem Pembelajaran Online - Evi Susilawati; Imamul Khaira; Hidayat Hidayat; Nurul Aini; Ali Ali; Zuraidahadlina Zuraidahadlina (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2023)
The geographical condition of Medan City which is prone to flooding requires the readiness of various parties to overcome it. One way to anticipate that the community is always prepared for disasters is to develop a disaster curriculum. Based on these conditions, this research is motivated by the importance of the Automated Short Essay Scoring (ASES) assessment model as a model for assessing the Disaster Curriculum. The purpose of this research is to develop an ASES assessment model as an assessment model in the disaster curriculum in online learning. The analytical method in this study is Research and Development (RD) which uses a mixed approach. This research develops software with stages: (1) needs analysis and (2) assessment model design, (3) expert validation, (4) product revision, and (5) implementation. The results of the research can be stated as follows: (1) the development of the ASES assessment model as an assessment model in the disaster curriculum in the online learning system has provided solutions in online learning activities. This research activity begins with a preliminary study in the form of needs analysis; (2) At the design stage of writing a program to produce an initial prototype product, (3) at the expert validation stage; and (4) results of the validation of the ASES assessment model on the content aspect of the instrument obtaining a score of 4.69 (very good category), the virtual aspect obtaining a score of 4.29 (good category), and the programming aspect obtaining a score of 4.63 (very good category)